Histopathologic Diagnosis of Atrophic Gastritis and Intestinal Metaplasia - Do Youn Park (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Atrophic gastritis and intestinal metaplasia are well-known to be reliable indicators of gastric cancer risk. They are clinically important in deciding whether to recommend endoscopic surveillance. Herein I review the histopathologic diagnosis of atrophic gastritis and IM. Gastric atrophy is divided into metaplastic atrophy and non-metaplastic atrophy. IM is categorized as complete (type I) and incomplete (type II, III). Systematic interpretation of gastric atrophy and IM using the updated Sydney system or operative link on gastritis assessment is recommended. Furthermore, I suggest using the consensus definition of gastric atrophy and incomplete IM in the gastric biopsy pathology report to support the surveillance of high-risk gastric cancer group.